Competition, Innovation, and Growth in Japan - Honjo, Yuji (Springer, 2017)
This book addresses three important concepts in the economy--competition, innovation, and growth--using various cases and available data in Japan and other countries. First, the authors discuss competition, including global competition, to provide a better understanding of competition policy in Japan. Then, the authors examine the effects of human capital and alliance on innovation while providing new innovation indicators. Moreover, the authors examine growth from the perspective of corporate strategy such as acquisition, including international comparison. The interplay of competition, innovation, and growth has been prevalent in Japan, and it still acts as a catalyst for stimulating the stagnant economy. A better understanding of competition, innovation, and growth provides the tools to reinvigorate the stagnant economy in Japan and to reinforce the economy in other countries where the period of rapid growth has ended.
Keywords: Economics -- Japan.; Economic development -- Japan.; Competition -- Japan.; Japan.; elektronické knihy; electronic books